Thyroid Hormones in Sediment and Water: Method Validation and Detection in Taihu Lake of China - Zhang, Shuzhan; Zhang, Jiaxin; Chang, Hong; Sun, Fuhong (Frontiers in Environmental Science, 2021)
Study of the occurrence and fate of thyroid hormones in aquatic environments requires a highly sensitive method that is capable of detecting such compounds at sub-ng/L concentrations. By using isotope-dilution UPLC-MS/MS, we developed a sensitive method for quantifying thyroxine (T4), 3,3ʹ,5-triiodothyronine (T3), 3,3ʹ,5ʹ-triiodothyronine (rT3), iodotyrosine (MIT), and 3,5-diiodotyrosine (DIT) in lake water and sediment samples. MIT and DIT were first reported in aquatic environments in this study and were detected in all sediment and water samples with concentrations of 0.01-1.1 ng/g dw and 1.9-9.9 ng/L, respectively. T4 was only observed in sediment, with the measured concentrations and frequency of